Eliminating mitochondrial DNA competition for nuclear DNA primers. - Zullo, S; Kennedy, J L; Gelernter, J; Polymeropoulos, M H; Tallini, G; Pakstis, A J; Shapiro, M B; Merril, C R; Kidd, K K (Genome Research, 1993)
Mitochondrial DNA (mtDNA) sequences were synthesized with nuclear DNA (nucDNA) sequence-tagged site (STS) primers by mismatch priming in three independent studies of the human nuclear genome. Mismatch primer binding sites on the mtDNA were identified with from 6- to 10-bp identity at the 3' ends of the primers. In two of three cases, single-stranded mtDNA copies were gel-isolated with intended nucDNA PCR products. During routine screening of the STSs, the radiolabeled gel-isolated products hybridized to polymorphic mtDNA restriction fragments. Intense signals after overnight exposure of radiolabeled PCR probes on Southern blots suggest contaminating mtDNA PCR products. The theoretical annealing temperatures of the mismatches were well below the annealing temperatures of the PCR primers, demonstrating annealing reactions driven by the molar surplus of the primers, that is, mass action. The probability that two primers (either one of a pair or both), designed to amplify nucDNA, will bind to and amplify mtDNA may be as high as 1 in 64, assuming that an identical match with only the 3' hexanucleotide is sufficient for amplification. To circumvent this problem we have developed OLIGFIND, a program that has identified the 104 of 4096 possible hexamers that are not present in human mtDNA. Our results suggest that time could be saved by designing STS primers with one of these 104 hexamers at the 3' end. OLIGFIND can also evaluate primer 3' ends for potential PCR products from mtDNA.